Towards a Healthy Ganga—Improving River Flows Through Understanding Trade Offs - Kaushal, Nitin; Babu, Suresh; Mishra, Arjit; Ghosh, Nilanjan; Tare, Vinod; Kumar, Ravindra; Sinha, Phanish Kumar; Verma, Ram Ujagir (Frontiers in Environmental Science, 2019)
WWF-India along with its partners is working towards the conservation of Ganga since last decade. During 2015-16, along with partners, WWF-India conducted an action research study in over 2 million hectare of culturable command area of two irrigation systems taking off from River Ganga, to understand the barriers to implementation of Environmental Flows (E-Flows) in the Ganga. Under this initiative, the team tried to bridge the knowledge gap about potential trade-offs for implementation of E-Flows in a critical stretch of Ganga. The team made an attempt to understand the surface water allocation and water use scenario in western and central part of the state of Uttar Pradesh, where the Ganga water is used for agriculture purpose through major irrigation infrastructure. The E-Flows recommendations for critical locations downstream of two barrages, i.e. head-works of two major irrigation schemes, were developed. A framework was developed to assess the costs and benefits of various flow regimes. Such a framework helps discuss the trade-offs emerging from E-Flows releases onto other committed allocations across various users. This paper discusses approaches for management of trade-offs to restore E-Flows in this stretch of Ganga, and include various management options – like (i) promotion of irrigation water use efficiency, (ii) gradual and marginal shift in land towards less-water intensive crops and (iii) institutional aspects. The paper argues that, whilst there is a widespread apprehension that, any curtailment in the allocation quota for irrigation would lead to adverse impact onto the farming community; but actually after assessing the trade-offs, it can be inferred that, the E-Flows implementation in this stretch of Ganga would require enhancement of water in the river, but that requirement is not substantial. Towards the end of the paper, challenges and opportunities for E-Flows implementation in the Upper Ganga are discussed. This paper attempts to discuss one of the newer approach in which, economic analysis has been used to articulate the rational for implementation of E-Flows regime.